Differences in the impact of harmonic distortion due to the installation of electronic load controller in self-excited induction generator and synchronous generator - Refdinal Nazir; Syafii Syafii; Andi Pawawoi; Fajril Akbar; Axel Doriza (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
In general, the application of Self-Excited Induction Generator (SEIG) or Synchronous Generator (SG) on the Stand-Alone Micro Hydel Power Plant (MHPP) is equipped with Electronic Load Controller (ELC) to control generator output during variations in consumer load. One type of ELC that is cheap and rigid developed today is the ELC, which is constructed by the uncontrolled bridge rectifier with DC Chopper. Based on the operational concept, basically this type of ELC can be implemented on both SEIG and SG, but both of these generators will have a different harmonic distortion effect on the output and its load. This paper examines the differences in the effects of harmonic distortions due to ELC installation on SEIG and SG. The initial stage of this study was to design the ELC developed. Then, the harmonic distortion response due to the installation of ELC on SEIG and SG is tested, which includes harmonic distortion in: stator current, PCC voltage, and consumer load current. THDI (Current Total Harmonic Distortion) stator current at SEIG with ELC has shown an average value smaller than the THD stator current in SG with ELC. Likewise, the THDV (Voltage Total Harmonic Distortion) value of PCC voltage and THDI value of the current consumer load on SEIG equipped with ELC has been shown to be smaller than the THDV value of PCC voltage and THDI value of the current consumer load on SG equipped with ELC. The effects of harmonic distortions due to the installation of ELCs that developed in this study on SEIG is still within the permitted limits, while on the SG, the harmonic distortion reduction is needed at the generator output.